2013
DOI: 10.1017/s002221511300073x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucocorticoids on nasal polyposis, with detection of inflammatory response by measurement of nitric oxide levels in nasal polyp tissue

Abstract: This study demonstrates the favourable effects of glucocorticoids on nasal polyposis, and alteration in nitric oxide tissue levels post-treatment. Nitric oxide level in nasal polyp tissue could be an indicator of treatment response, and may aid surgical decision-making by detecting cases that probably will not respond to medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another trial considered oral GCS versus placebo as an adjunct to treatment with intranasal GCS in CRSwNP patients [65]. This study recruited 30 participants and was considered at high risk of bias because of lack of blinding and lack of information on randomization.…”
Section: Evidence For Efficacy Of Systemic Gcs In Different Inflammatmentioning
confidence: 99%
“…Another trial considered oral GCS versus placebo as an adjunct to treatment with intranasal GCS in CRSwNP patients [65]. This study recruited 30 participants and was considered at high risk of bias because of lack of blinding and lack of information on randomization.…”
Section: Evidence For Efficacy Of Systemic Gcs In Different Inflammatmentioning
confidence: 99%
“…The mechanism of corticosteroid action may be a multifactorial effect on various aspects of the inflammatory reaction, initiated by steroid binding to a specific cytoplasmic glucocorticoid receptor. 28 Specific effects of fluticasone furoate seen in experimental sensitized rats included activation of the glucocorticoid response element, inhibition of transcription factors such as nuclear factor kappa-B (NFκB), and inhibition of antigen-induced eosinophilia. 29 Our previous investigation demonstrated that RANTES levels in nasal secretions could be a useful path in the assessment of effects of macrolide antibiotic treatment in both allergic and nonallergic patients with nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…38 Additionally, the included studies focused on the resolution of individual symptoms instead of overall effect on quality of life or endoscopic exams, and did not identify if an underlying CRS condition was present. 20,39 A recent study by Ho et al showed that patients with eosinophilic CRSwNP and aspirin sensitivity tend to require systemic therapy with OCS and/or biologic agents after ESS because of acute exacerbation of the disease in the postoperative setting. 40 However, no study has reviewed INCS in addition to OCS in the immediate postoperative setting for CRSwNP patients with positive bacterial cultures.…”
Section: Discussionmentioning
confidence: 99%